Spark Plasma Sintering of Copper-Niobium-Graphite Composites, and the Investigations of Their Microstructure and Properties - Azunna Agwo Eze; Emmanuel Rotimi Sadiku; Williams Kehinde Kupolati; Julius Musyoka Ndambuki; Jacques Snyman; Idowu David Ibrahim (Metals, 2022)
The microstructures and properties of ternary copper-niobium-graphite (Cu-Nb(nano)10-C4, and Cu-Nb(micron)10-C4) composites produced via spark plasma sintering (SPS) technique have been investigated for their potential use as electrical connection materials at high-temperature application. Nowadays, there is much activity in the development of such material all over the world. This study was aimed to compare the effect of adding the nano and micron particles sizes of Nb powders in the microstructures and properties of Cu-Nb-C composites sintered at 700 and 650 °C temperatures. The investigated materials have been produced via the SPS method. The microstructures were observed by electron microscopy technique, the wear test was observed by Anton-Paar TRB3 tribometer, thermal diffusivity was observed by LFA427 NETzschlaser flash device within the temperature of 100–900 °C, and the corrosion test was performed by potentiodynamic polarization. The discoveries have been presented in the manuscript and were discussed with reference to the microstructure development, the composite with nanoparticles sintered at 650 °C displayed closed thermal stabilities as temperature increased, and it recorded a low coefficient of friction and suitable corrosion resistance, which correspond to requirements for electrical contacting materials. The SPS method of production of the composites caused initial microstructure refinement and improved the properties of the composites.